QUALITY OF LIFE ON ELDERLY: A STUDY ON PRIMARY HEALTH ATTENTION - Melina da Costa Nicolazi; Juliana Krum Cardoso da Silva; Luciana Coelho; Andreia Morales Cascaes; Fátima Büchele (Universidade Federal do Paraná, 2009)
The objective was to identify the levels and perceptions of quality of life among elderly people in a communityfrom the city of Florianópolis in Santa Catarina. A number of 106 older adults between 60 and 80 years were interviewed athome. Information on sex, age, education level, marital status and self-rated health status were collected and the WHOQOL-OLD instrument from World Health Organization was used to assess the quality of life. Among the elderly respondents,73.58% were female. The average age was of 69.25 years. Poor self-rated health status was reported by 14.15% of theinterviewees. The quality of life among the majority of elderly investigated presents a satisfactory level. However, for thefear pain before death and the impairment to senses affecting daily life, a considerable proportion reported dissatisfaction,50% and 71.7%, respectively.